L'institution oratoire du Prince ou le savoir au service du bien dire - Roy, Roxanne (Renaissance and Reformation / Renaissance et Réforme, 2008)
Conceived somewhat in the style of the 'Mirrors of Princes' tradition composed of educational tracts addressed to future monarchs dating back to the 9th century, these late sixteenth-century treatises of royal eloquence are intended to serve the Prince and edify his speech. For this reason, they invite examination as princely 'Institutions of Oratory'. The ideal portrait of the king, forever haunted by a general fear of conferring royalty upon an ass, is one of a 'learned and well-spoken' prince. Education and eloquence therefore constitute two royal virtues which allow the sovereign to distinguish himself from the people and render himself worthy of the admiration of all subjects. This primary relation between learning and eloquence taken as fundamental elements of royal power is the main concern of the present study and analysis. We shall examine the case of three 'rhetorics', composed for the use of Henry III with the intention of informing himself as a model of the 'well-spoken king'.